2015
DOI: 10.1192/bjp.bp.114.152520
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative care for patients with bipolar disorder: randomised controlled trial

Abstract: When compared with treatment as usual, collaborative care substantially reduced the time participants with bipolar disorder experienced depressive symptoms. Also, depressive symptom severity decreased significantly. As persistent depressive symptoms are difficult to treat and contribute to both disability and impaired quality of life in bipolar disorder, collaborative care may be an important form of treatment for people with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 38 publications
(67 reference statements)
1
16
1
Order By: Relevance
“…Another included a combination of CBT plus psychoeducation and reported that it was more effective in comparison to TAU in 40 refractory BD patients concerning hospitalization and residual symptoms at 12 months follow-up [ 27 ]. A collaborative care study on 138 patients and follow-up of 12 months also gave positive results [ 48 ]. One multicentred Italian study assessed the efficacy of the Falloon model of psychoeducational family intervention (PFI), originally developed for schizophrenia management and adapted to BD-I disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another included a combination of CBT plus psychoeducation and reported that it was more effective in comparison to TAU in 40 refractory BD patients concerning hospitalization and residual symptoms at 12 months follow-up [ 27 ]. A collaborative care study on 138 patients and follow-up of 12 months also gave positive results [ 48 ]. One multicentred Italian study assessed the efficacy of the Falloon model of psychoeducational family intervention (PFI), originally developed for schizophrenia management and adapted to BD-I disorder.…”
Section: Resultsmentioning
confidence: 99%
“…A second trial randomized 138 BD patients to receive collaborative care (contracting, psychoeducation, problem-solving treatment, systematic relapse prevention and monitoring of outcomes) vs. TAU. The results suggested that collaborative care had a significant and clinically relevant effect on the number of months with depressive symptoms, as well as on severity of depressive symptoms, but there was no effect on symptoms of mania or on treatment adherence [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of them have showed a positive effect on satisfaction with care and involvement in decision-making [ 13 – 15 ]. Only one randomized controlled study has evaluated the effectiveness of a collaborative care program (comprised several interventional modules including contracting, psychoeducation, problem-solving treatment or monitoring of outcomes) on symptoms and medication adherence in BD patients experiencing depressive symptoms, in comparison with CAU [ 48 ]. The intervention group showed significant reduction of depressive symptom severity at 12 months ( p = 0.004), with no effect on treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The results from a RCT ( n = 138) indicated that collaborative care significantly decreased the severity of depressive symptoms from a mean QIDS (Quick Inventory for Depressive Symptomatology) score of 10.5 to 8.4 at the end of the one-year trial period. 21 Additionally, collaborative care decreased the time patients spent with depressive symptoms. The patients in the intervention group spent an average 3.2 months with depressive symptoms during the six months prior to randomization.…”
Section: Literature Reviewmentioning
confidence: 99%